PENGARUH KOMITMEN DAN MOTIVASI BERPRESTASI TERHADAP KINERJA GURU SMA NEGERI 56 JAKARTA - Masudi Masudi (Universitas Mercu Buana, 2014)
Abstract: The purpose ofthis study was to determine the effect of commitment and achievement motivation on teacher performance. Descriptive quantitative research method using correlation and multiple regression statistics with the aim of analyzing the influence of two independent variables on the performance of teachers. The sampleused was the entire population of teachers as respondents. The results showed that the commitment and achievement motivation affect the performance of teachers. From the results of analysis, the influence ofthe two variables is quite strong .The result also evidenced from the F test and t-test, which states that both partially and simultaneously effect very significant on the performance of teachers. The results ofthis study, whencompared with previous research, the study supports previous research conducted. Where the teacher's performance is affected by factors of commitment and achievementmotivation.Keywords: Commitment, Achievement Motivation, Teacher Performance